The Relations Between Religion and Politics in European Education Systems - Fabretti, Valeria; Paola, Nadia Di (SCAD Independent, 2017)
This paper aims to discuss the role of religion in contemporary European education systems, especially in the realm of social rights. This article has been removed from our publication.